A Randomized Controlled Trial for the Effectiveness of Aromatherapy in Decreasing Salivary Gland Damage following Radioactive Iodine Therapy for Differentiated Thyroid Cancer. (30th November 2016) - Nakayama, Michihiro; Okizaki, Atsutaka; Takahashi, Koji
Abstract : Objective. The aim of this study was to investigate effects of aromatherapy in decreasing salivary gland damage for patients undergoing radioactive iodine (RAI) therapy with differentiated thyroid cancer (DTC). Materials and Methods. The subjects were 71 patients with DTC. They were divided into aromatherapy group (group A, n = 35 ) and a control group (group B, n = 36 ). We blended 1.0 mL of lemon and 0.5 mL of ginger essential oils. The patients in the inhalation aromatherapy group inhaled this blend oil and those in the control group inhaled distilled water as placebo for 10 min during admission. We statistically compared salivary gland function before and after treatment between groups A and B. Results. In comparison with group B, the rate of change of the accumulation rate was significantly higher in the parotid glands and submandibular glands of group A (P < 0.05 ). In comparison with group B, a significant increase in rate of secretion change before and after treatment was noted in the bilateral parotid glands in group A (P < 0.05 ). Conclusion. Because an amelioration of salivary gland function was observed in the present study, our results suggest the efficacy of aromatherapy in the prevention of treatment-related salivary gland disorder. This trial is registered with UMIN Clinical Trial Registry: UMIN000013968 .